Workshop on Nata de PiLang Production and Education on Vitamins and Natural Ingredients for Anemia Prevention Among Students of Sultan Agung 3 Islamic Senior High School Semarang - Wilda Fhitriany Usman; Rissa Maharani Dewi; Tri Diana Puspita Rini; Ulya Rahmana; Liliana Meilani Putri (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2026)
Anemia is a global health problem that remains prevalent among adolescents, primarily due to iron deficiency and inadequate intake of essential micronutrients. The prevalence of anemia among adolescents in developing countries is reportedly high and impacts cognitive abilities, productivity, and quality of life. Efforts to prevent anemia require a practice-based educational approach that is easy to understand and applicable. This community service activity aims to improve students' knowledge and skills through education on anemia, vitamins, and the use of natural ingredients in the form of a functional food innovation, Nata de PiLang (pineapple and butterfly pea flower). Methods used included lectures, interactive discussions, and product-making demonstrations. Evaluation was conducted through pretests and posttests and participant observation. The results of the activity showed an increase in students' knowledge about anemia and the role of vitamins in iron absorption, as well as improved skills in making fermented products. The use of natural ingredients such as pineapple, which is rich in vitamin C, has been shown to potentially increase iron absorption and support anemia prevention. This activity is effective in improving adolescent health literacy and is expected to become a model for practice-based education in anemia prevention efforts in schools.